The Comparison Of Student’s Ability In Understanding The English Reading Text By Using Skimming And Scanning Technique - Semaria Eva Elita Girsang; Ella Damayanti (Program Studi Pendidikan Bahasa Inggris FKIP, 2022)
The aim of this research was to find out the effectiveness of using skimming and scanning technique and find out which technique is better skimming or scanning on students’ ability in understanding the English reading text of the tenth grade students at MAS Al Washliyah Serbalawan in the academic year 2021/2022. This research used quantitative approach with pre - experimental design. The data were obtained by using post-test only. The data of post-test was analyzed by using descriptive and inferential statistics. (SPSS 23.0). The result of the research shows that the testing hypothesis of post-test scores was found that tcount = 2.668 ˃ ttable = 1.684 at the significance level α=0,05 with the degrees of freedom (df)=39, So, Ho is rejected and Ha is accepted. It means that the implementation of Scanning and skimming effect on students reading ability at tenth grade of MAS Al Washliyah Serbelawan in academic year 2021/2022